Financial considerations of South African environmental problems - Miltz, David (Department of Environmental and Geographical Science, 2023)
No panacea exists for the resolution of environmental problems. In South Africa environmental control is affected almost exclusively by way of direct prohibition an~ regulation. These policies have serious limitations predominantly as a result of legal and administrative inadequacies. The remedy of these inadequacies is not feasible and alternative, complementary or replacement control policies are needed. This report reviews a number of alternative policies, most of which rely on market related mechanisms, in the context of pollution, resource destruction and land use problems. In addition, current financial legislation is replete with provisions contributing towards the exacerbation of environmental ills. These anomalous provisions must be re-evaluated in terms of material objectives, which must include the need for sound environmental resource management. A number of provisions do, however, offer some potential for conservation activities. These provisions, together with some innovative schemes, are introduced in the report and deserve further research.